DESAIN SITUS WEB SEBAGAI MEDIA INFORMASI DAN PROMOSI PADA ESSY’S BROWNIES SEMARANG - A. H. B. Nurmana M. S; Tri Adhi Wibowo (STEKOM PRESS, 2018)
Internet customers and users in Indonesia are expressed from year to year continues to grow. It can be seen from the graph that is processed based on data from the Indonesian Internet Service Providers Association (APJII) and the Central Statistics Agency (BPS), that internet customers and users are increasing every year. The usefulness and benefits of the website include making it easier to exchange and update information with other internet users, and to be able to obtain up-to-date information. A website is the work of individuals or individuals, can also show ownership of an organization, company, and usually the website shows some special topics or specific interests.